(untitled) (Mantichora. Italian Journal of Performance Studies, 2020)
The present essay investigates the settlement process of a Roma community in the Sicilian Town of Mazara del Vallo. It suggests that, in spite of the high levels of discrimination, the Roma community became part of the national underclass, and that the integration within this class takes place through a set of informal practices involving the community and the State. The author describes the trajectory followed by this community in the aftermath of the Kosovo war of the 1990s, and reflects on some elements apt to generate a theory of action concerning the relation between individuals and the State.